Addressing Moral Suffering in Police Work: Theoretical Conceptualization and Counselling Implications - Papazoglou, Konstantinos; Blumberg, Daniel M.; Kamkar, Katy; McIntyre-Smith, Alexandra; Koskelainen, Mari (Canadian Journal of Counselling and Psychotherapy, 2020)
Moral distress is a condition affecting police officers who, because of insurmountable circumstances (e.g., not being able to protect a civilian from a violent criminal) or bad judgement (e.g., crossfire between officers), believe that they did not do enough or did not do the “right thing.” Moral injury occurs when police officers perpetrate, fail to prevent, or bear witness to deaths or severe acts of violence that transgress deeply held moral beliefs (e.g., fatally shooting an allegedly armed criminal who is later proved to be unarmed). Considering the multidimensional nature of police work, several authors have maintained that it is imperative to understand the complex nature of police moral suffering (i.e., moral distress and moral injury). This review highlights the importance of assessing and recognizing moral injuries and/or distress among police officers. The data indicates that counsellors should build relevant, empirically validated interventions into their counselling treatment plans. Moreover, researchers have suggested that counsellors employ practice-based and evidence-based techniques with officers who experience moral suffering. Ultimately, recommendations for future research are provided, considering that research in this area is in its infancy.